2018
DOI: 10.1002/cbdv.201800093
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Phenolic Content, Profile, and Antioxidant Activity of Seeds among Different Paeonia ostii Cultivated Populations in China

Abstract: The purpose of this study was to analyze the phenolic profiles of seeds from fifteen Paeonia ostii cultivated populations in China and identify their relationship with antioxidant activities and associated environmental factors. Thirteen individual phenolic compounds were quantitatively determined by HPLC, and (+)-catechin was the most abundant phenolic compound in the seeds. Correlation analysis showed that phenolics were the most effective antioxidant compound class by evaluating DPPH, ABTS, and hydroxyl rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
1
20
2
Order By: Relevance
“…From the view of chemical classification, P. ostii is a stable chemotype. [10,[29][30][31] Its chemical composition does not vary due to artificial measures, geographical differences or external environmental factors, which may also be the reason for producing stable fatty acid composition types.…”
Section: Discussionmentioning
confidence: 99%
“…From the view of chemical classification, P. ostii is a stable chemotype. [10,[29][30][31] Its chemical composition does not vary due to artificial measures, geographical differences or external environmental factors, which may also be the reason for producing stable fatty acid composition types.…”
Section: Discussionmentioning
confidence: 99%
“…Other secondary metabolites in plants, such as phenols, flavonoids, esters, terpenoids, can accelerate the antioxidant activity of tree peony seeds. [16,17] Meng et al [24] and Liu et al [25] found that antioxidant activity of Juniperus rigida was correlative to the abundant caryophyllene, α-caryophyllene, and caryophyllene oxide in essential oils of its stem, needles and berries. In summary, the antioxidant activity variations of plants are possibly caused by the contents, properties, and proportions of the phytochemical profiles.…”
Section: Bioactivity Of Different Tree Peony Cultivarsmentioning
confidence: 99%
“…Zhang et al [15] investigated the chemical compositions and antioxidant activities of essential oils from the petals of eleven cultivars and three wild species of tree peony, also determined the antioxidant activity in seeds of P. ostii cultivar and nine wild tree peony species using DPPH, ABTS and FRAP assays based on the investigation of phenolic compounds, and found that tree peony seeds extraction displayed high antioxidant activity, supporting a potential source for natural antioxidants with fine development prospect. [16,17] Currently, as an innovative and emerging woody oleaginous crop resource, tree peony is now being gradually developed and utilized more and more effectively in China, which attributed to its preeminent oil-use features characterized by abundant fatty acid profiles and high bioactivity. As an important oleagi-nous tree peony variety, P. ostii is now being planted with large-scale for oil extraction in China, which is recognized as a single tree peony cultivar and commonly called 'Fengdan' (FD).…”
Section: Introductionmentioning
confidence: 99%
“…Various phytochemicals, including phenolics [11,12], stilbenes [13], and terpenoids [14,15,16], were identified in tree peony in the previous studies. The phytochemical species and contents in tree peony differ according to the cultivars and organs involved [6,17,18,19]. Tree peony seeds exhibit strong antioxidant activity and phenolic compounds have been verified as the most important antioxidants [11,17,19].…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical species and contents in tree peony differ according to the cultivars and organs involved [6,17,18,19]. Tree peony seeds exhibit strong antioxidant activity and phenolic compounds have been verified as the most important antioxidants [11,17,19]. However, the phenolic profiles of the edible tree peony flower FDB have not been identified and the antioxidant properties have not yet been characterized.…”
Section: Introductionmentioning
confidence: 99%